Secure Data Transfer on Color Flower Image Using AES, GA and LSB - Ekta Chauhan (International Journal of Computing and Informatics (IJCANDI), 2016)
a new technique is going to be introducing for data transmission over internet. This research presented image steganography on color flower image using genetic algorithm (GA) and AES with LSB technique. In this paper secret data is encrypted and decrypted by AES is performed to high security. Then improved covert message is identified by GA. This proposed method is executed and key strength of this project is its huge data hiding capability and least distortion in Stego image. This technique is functional over various images and the outcomes show least distortion in altered image. PSNR and entropy help for experimental study.